Analysis of the company investment attractiveness - Tkachuk, V. V. (ТДАТУ, 2019)
The results of economic activity, financial condition of the enterprise depend not only on the availability and placement of assets (capital), but also on the efficiency of use, turnover and profitability of production means and assets of the enterprise as a whole.
Keywords: Agro-Service; online store; сapital investment